Computational Study on Polarisation Behaviour of Functionalised Endohedral Metallofullerenes - Halstead, M. J. (2023)
This work focused on investigating the potential for selected functionalised endohedral metallofullerene isomers to be viable candidates for a molecular polarisation switch, with a particular focus on the Ca@C60 system. This work combines classical electrostatic analysis and Density Functional Theory (DFT) to investigate the correlation between the encapsulated calcium metal ion position and distribution of surface charge that results in polarisation on the fullerene cage. In addition, the modification of internal potential energy barriers through functionalisation of the fullerene cage was investigated as a route to developing a bistable polarisation switch.